ANALISIS DAMPAK PELAKSANAAN FUNGSI PERENCANAAN DAN PENGAWASAN BELAJAR TERHADAP PRESTASI BELAJAR MAHASISWA PROGRAM STUDI PENDIDIKAN EKONOMI IKIP PGRI MADIUN - M.Th. Kuswariningsih (EQUILIBRIUM : Jurnal Ilmiah Ekonomi dan Pembelajarannya, 2013)
Students  evidently  often lose sight of the essence  of planning  and controlling on learning  practice,  in spite of knowing  that they  are influential  against  their  learning achievement.   This  research  serves  a thorough  out-look  on tbe impact  of planning  and controlling  functions  on learning  practice  carried  out by the students  of Department   of Economy  Teaching,  IKIP PGRI  MADIUN.  The subjects  of this research  are students  of Department   of Economy  Teaching,  IKIP PGRI  MADIUN,  with 50 of whom  have been chosen  to be the sample.  The method  of the research  is co relational  descriptive  study posing  the relationship   among variables.  The data are drawn  by means of questionnaire and documentation.   The data analysis  is carried  out to have r-test, F-test and t-test aided with SPSS for Windows V L6.0. The analysis  shows tbat there is significant  influence  of planning  and controlling  oftbe  learning practice  against the students achievement,  which is proven  by l"count>    rtable by 0.356  >   0.279.  The contribution   of planning  and controlling functions  against  the students'   achievement  is 12.75%, while  the rest of 75.5% belongs to other  factors.  The overall  result  shows  that planning  and controlling  functions  have significant  influence  against the students  achievement,  The F-test proves that F > F  bl by 3.407 > 3.23 or Sigcoun >t Sigprobby 0.042 > 0.05. there is a different  degree of significance of the planning  and comtrolling  function,  which  is proven  by tCOlloIlft 2.434 while ttableat the significance  degree of 5% and N 50 is 2.021 resulting  in tcoun > t ttableby 2.434 > 2.021  showing  the different  influence  of planning  and controlling  variables  against  the students  achievement.   Computation   against  controlling  yields tcouuot f 1.553 while ttablaet the significance  degree  of 50/0 and N 50 is 2.021. this means  that teOlil <= ttableby  1.553 < 2.021  having  no influence  of the planning  function  against  the students'   achievement. The t-test  yields  equation  ofY=2414   + 0.029X -      0.020X which  means  that when  the function  increases  by  1% the learning  achievement   will also increase  by 2.29%  if other factors are considered  constant.  When  controlling  function  increases  by  1% the learning achievement  will decrease  by 2.0% if other factors  are considered  constant.